2017
DOI: 10.1080/03630242.2017.1310169
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and gender minority breast cancer patients choosing bilateral mastectomy without reconstruction: “I now have a body that fits me”

Abstract: Sexual and gender minority (SGM) breast cancer patients have begun embracing the choice to "go flat" or opt out of reconstruction after bilateral mastectomy, though little is known about this population. SGM breast cancer survivors were identified through purposive and referral sampling and invited to participate in a web-based survey containing both closed- and open-ended items. Of the sixty-eight SGM breast cancer survivors aged 18-75 years who completed the survey between May 2015 and January 2016, 25 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 17 publications
1
54
0
Order By: Relevance
“…The present research was a cross-sectional study and therefore we cannot test the impact of breast reconstruction on quality of life, this could be clarified in a prospective study. The sexual orientation of patients has not been evaluated, and this may have interfered with the results, as the literature shows that women who identify themselves as lesbians or gays are generally not interested in reconstruction [20].…”
Section: Discussionmentioning
confidence: 99%
“…The present research was a cross-sectional study and therefore we cannot test the impact of breast reconstruction on quality of life, this could be clarified in a prospective study. The sexual orientation of patients has not been evaluated, and this may have interfered with the results, as the literature shows that women who identify themselves as lesbians or gays are generally not interested in reconstruction [20].…”
Section: Discussionmentioning
confidence: 99%
“…23 Women who choose to go flat describe experiencing negative assumptions or judgment from others, difficulty finding clothing that fits correctly, and repeated suggestions to pursue unwanted treatment. 23 There are currently no peer-reviewed studies regarding heteronormative women who choose to go flat. Regardless, practitioners should explore each woman's wishes and not make assumptions about the need for prosthetics or reconstruction.…”
Section: Breast Surgerymentioning
confidence: 99%
“…For WSW, having a partner was associated with better sexual function, greater sexual desire, better mental and physical health, and less fear of recurrence compared to heterosexual counterparts [15][16][17]19,21]. In addition, WSW reported being less focused on body image, suffered fewer identity issues due to breast cancer and chose not to have reconstruction more often than heterosexual peers [14,25,54]. However, WSW reported more challenges with access to care [23] and experienced more physical complications related to mastectomy and radiation than heterosexual peers [18].…”
Section: Breast Cancer Survivorshipmentioning
confidence: 98%
“…Only four studies included transgender and/or genderqueer respondents [25,54,57,59]. Bryson et al [54] found that intersectional identities impacted the experiences of transgender cancer survivors.…”
Section: Transgender Cancer Survivorshipmentioning
confidence: 99%
See 1 more Smart Citation